Sumber Air dalam Ruang Budaya Masyarakat Desa Toyomerto Singosari, Malang - Titisari, Ema Yunita; Antariksa, -; Wulandari, Lisa Dwi; Surjono, - (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment), 2018)
In the end of Majapahit period, Buddhism built a sacred building near Sumberawan water source in Toyomerto village, with aims to strengthen the efficacy and ‘transform’ the water to be tirta amerta (sacred water). In addition to the holiness of the water and the use of the water for ritual ceremony, Sumberawan water is also used for irrigation and the daily needs of the villagers. Every year the villagers commemorate Slametan Banyu (ceremony for the water). This study highlights significance of the water source in the cultural space of Toyomerto Village, and the efforts to maintain its sustainability. This study used qualitative-descriptive methods with anthropological-historic and anthropological- ecology approaches. From the data, discourse analysis examined the water resources from the perspective of cultural attributions. The result shows that the effort of Toyomerto villagers in maintaining sustainability of the water source do not merely result from physical effort but also by transcendental commitment. The establishment of the temple, myths, and folklores are believed by the people to prevent the water source from damage. In conclusion, water sustainability should be maintained for a balance of vertical-transcendental and horizontal-social relationships. Keywords: water resources, rites, cultural space